Beyond the Screen: Student’s Voices on eLearning - Nurhaliza, Siti; Ramadhani, Diva; Efnawati, Yulia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores students’ perceptions of using eLearning technologies at SMAN 2 Tanjungpinang, aiming to understand the types of digital tools students use, their proficiency levels, and their attitudes toward integrating technology into learning. Using a quantitative descriptive method, data were gathered through a structured questionnaire distributed to 45 students. The survey focused on their use of devices, applications, and software related to eLearning, assessing both familiarity and confidence. Results indicate that while students generally view eLearning technologies positively—especially those that are user-friendly and accessible—their digital proficiency varies widely depending on the tool. Smartphones emerged as the most confidently used device, with 66.7% of students identifying as advanced users, likely due to their daily integration and ease of use. In contrast, only 6.8% reported advanced skills in using computers, and just 9.1% for tablets, suggesting a need for greater focus on these essential academic tools. Similarly, students demonstrated strong skills in general digital tools like search engines, but much lower proficiency with educational apps such as Duolingo and quizziz, where 62.2% were beginners. While platforms like TikTok, Instagram, and Google saw high user confidence, engagement with formal educational tools and productivity platforms was limited. These findings highlight a clear gap in academic digital literacy and emphasize the need for targeted digital education initiatives to better prepare students for technology-integrated learning environments.